Biochars improve agricultural production: The evidence base is limited - Vincent CHAPLOT; Philippe BAVEYE; René GUENON; Elie LE GUYADER; Budiman MINASNY; Anoop Kumar SRIVASTAVA (Pedosphere, 2025)

Cover crop studies: The need for more reliable data - Vincent Chaplot; Pete Smith (Global Change Biology, 2024)

Cover crops do not increase soil organic carbon stocks as much as has been claimed: What is the way forward? - Vincent Chaplot; Pete Smith (Global Change Biology, 2023)
When compared to virgin land (forest and grassland), croplands store significantly lower amounts of organic carbon (OC), mainly as a result of soil tillage, and decreased plant inputs to the soil over the whole year. Doubts have been expressed over how much reduced and zero tillage agriculture can increase OC in soils when the whole soil profile is considered. Consequently, cover‐crops that are grown in‐between crops instead of leaving soils bare appear as the “last man standing” in our quest to enhance cropland OC stocks. Despite the claim by numerous meta‐analyses of a mean carbon sequestration rate by cover crops to be as high as 0.32 ± 0.08 ton C ha −1 year −1 , the present analysis showed that all of the 37 existing field studies worldwide only sampled to a depth of 30 cm or less and did not compare treatments on the basis of equivalent soil mass. Thirteen studies presented information on OC content only and not on OC stocks, had inappropriate controls ( n = 14), had durations of 3 years or lower ( n = 5), considered only one to two data points per treatment ( n = 4), or used cover crops as cash crops (i.e., grown longer that in‐between two crops) instead of catch crops ( n = 2), which in all cases constitutes shortcomings. Of the remaining six trials, four showed non‐significant trends, one study displayed a negative impact of cover crops, and one study displayed a positive impact, resulting in a mean OC storage of 0.03 ton ha −1 year −1 . Models and policies should urgently adapt to such new figure. Finally, more is to be done not only to improve the design of cover‐crop studies for reaching sound conclusions but also to understand the underlying reasons of the low efficiency of cover crops for improved carbon sequestration into soils, with possible strategies being suggested.

Cropping leads to loss of soil organic matter: How can we prevent it? - Vincent CHAPLOT; Pete SMITH (Pedosphere, 2023)

Long‐term (64 years) annual burning lessened soil organic carbon and nitrogen content in a humid subtropical grassland - Khatab Abdalla; Pauline Chivenge; Philippe Ciais; Vincent Chaplot (Global Change Biology, 2021)
Burning has commonly been used to increase forage production and nutrients cycling in grasslands. However, its long‐term effects on soil organic carbon (SOC) and nitrogen (N) pools within the aggregates and the relation between aggregates‐associated SOC and soil CO 2 emissions need further appraisal. This study evaluated the effects of 64 years of annual burning on SOC and N dynamics compared to annual mowing and undisturbed treatments in a grassland experiment established in 1950. Soils were sampled from four depths representing the upper 30 cm layer and fractionated into macroaggregates, microaggregates and silt + clay fractions. The macroaggregates were further fractionated into three occluded fractions. The SOC in the bulk soil and aggregates were correlated to soil CO 2 effluxes measured under field conditions. Compared to the undisturbed treatment, annual burning decreased aggregates stability, SOC and N in the upper 30 cm layer by 8%, 5% and 12%, respectively. Grassland mowing induced greater aggregates stability than burning only in the upper 5 cm. Burning also decreased SOC in the large macroaggregates (e.g., 0–5 cm) compared to mowing and the undisturbed grasslands but proportionally increased the microaggregates and their associated SOC. Soil N associated with aggregates decreased largely following grassland burning, for example, by 8.8‐fold in the microaggregates within the large macroaggregates at 20–30 cm compared to the undisturbed grassland. Burning also increased soil CO 2 emissions by 33 and 16% compared to undisturbed and mowing, respectively. The combustion of fresh C and soil organic matter by fire is likely responsible for the low soil aggregation, high SOC and N losses under burned grassland. These results suggested a direct link between grass burning and SOC losses, a key component for escalating climate change severity. Therefore, less frequent burning or a rotation of burning and mowing should be investigated for sustainable grasslands management.

Temporal response of soil organic carbon after grassland‐related land‐use change - Wei Li; Philippe Ciais; Bertrand Guenet; Shushi Peng; Jinfeng Chang; Vincent Chaplot; Sergey Khudyaev; Anna Peregon; Shilong Piao; Yilong Wang; Chao Yue (Global Change Biology, 2018)
The net flux of CO 2 exchanged with the atmosphere following grassland‐related land‐use change ( LUC ) depends on the subsequent temporal dynamics of soil organic carbon ( SOC ). Yet, the magnitude and timing of these dynamics are still unclear. We compiled a global data set of 836 paired‐sites to quantify temporal SOC changes after grassland‐related LUC . In order to discriminate between SOC losses from the initial ecosystem and gains from the secondary one, the post‐ LUC time series of SOC data was combined with satellite‐based net primary production observations as a proxy of carbon input to the soil. Globally, land conversion from either cropland or forest into grassland leads to SOC accumulation; the reverse shows net SOC loss. The SOC response curves vary between different regions. Conversion of cropland to managed grassland results in more SOC accumulation than natural grassland recovery from abandoned cropland. We did not consider the biophysical variables (e.g., climate conditions and soil properties) when fitting the SOC turnover rate into the observation data but analyzed the relationships between the fitted turnover rate and these variables. The SOC turnover rate is significantly correlated with temperature and precipitation ( p p > 0.05). Comparing our results with predictions from bookkeeping models, we found that bookkeeping models overestimate by 56% of the long‐term (100 years horizon) cumulative SOC emissions for grassland‐related LUC types in tropical and temperate regions since 2000. We also tested the spatial representativeness of our data set and calculated SOC response curves using the representative subset of sites in each region. Our study provides new insight into the impact grassland‐related LUC on the global carbon budget and sheds light on the potential of grassland conservation for climate mitigation.

Evaluating DEM source and resolution uncertainties in the Soil and Water Assessment Tool - Shengpan Lin; Changwei Jing; Neil A. Coles; Vincent Chaplot; Nathan J. Moore; Jiaping Wu (Stochastic Environmental Research and Risk Assessment, 2013)

Soil organic carbon stocks in Laos: spatial variations and controlling factors - VINCENT CHAPLOT; BOUNTHONG BOUAHOM; CHRISTIAN VALENTIN (Global Change Biology, 2010)
Surface soils, which contain the largest pool of terrestrial organic carbon (C), may be able to sequester atmospheric C and thus mitigate climate change. However, this remains controversial, largely due to insufficient data and knowledge gaps in respect of organic C contents and stocks in soils and the main factors of their control. Up to now and despite numerous evaluations of soil organic carbon (SOC) stocks worldwide, the sloping lands of southeast Asia, one of the most biogeochemically active regions of the world, remain uninvestigated. Our main objective was to quantify SOC stocks and to evaluate the impact of various environmental factors. We, therefore, selected Laos with 230 566 km 2 of mostly forested steep slopes, and where cultivation is still mainly traditional, i.e. a system of shifting cultivation without fertilization or mechanical tillage. Analytical data from 3471 soil profiles demonstrated that the top 1 m of soil depth holds an estimated 4.64 billion tons of SOC, 65% of which is in the first 0.3 m. SOC stocks to 0.3 m exhibit a high coefficient of variation (CV=62%) with values from 1.8 to 771 Mg C ha −1 and a mean at 129 Mg C ha −1 . Furthermore, these stocks are significantly (at P t ‐tests with the largest amount being found under forest, less under shifting cultivation and the smallest under continuous cultivation. Moreover, SOC stocks correlated regionally to total annual rainfalls and latitude, and locally at the hill‐slope level to the distance to the stream network and the slope angle. It is hypothesized that this correlation is through actions on mineral weathering, soil clay content, soil fertility and SOC redistributions in landscapes. These relationships between SOC stocks and environmental factors may be of further use in (1) predicting the impact of global changes on future SOC stocks; and (2) identifying optimal strategies for land use planning so as to minimize soil C emissions to the atmosphere while maximizing carbon sequestration in soils.

Nitrate Depletion During Within-Stream Transport: Effects of Exchange Processes Between Streamwater, the Hyporheic and Riparian Zones - Catherine Grimaldi; Vincent Chaplot (Water, Air, & Soil Pollution, 2000)